Repertoire of Epitopes Recognized by Serum IgG from Humans Vaccinated with Herpes Simplex Virus 2 Glycoprotein D - Whitbeck, J. Charles; Huang, Zhen-Yu; Cairns, Tina M.; Gallagher, John R.; Lou, Huan; Ponce-de-Leon, Manuel; Belshe, Robert B.; Eisenberg, Roselyn J.; Cohen, Gary H. (Journal of virology, 2014)
The results of a clinical trial of a subunit vaccine against genital herpes were recently reported (R. B. Belshe, P. A. Leone, D. I. Bernstein, A. Wald, M. J. Levin, J. T. Stapleton, I. Gorfinkel, R. L. Morrow, M. G. Ewell, A. Stokes-Riner, G. Dubin, T. C. Heineman, J. M. Schulte, C. D. Deal, N. Engl. J. Med. 366: 34–43, 2012, doi:10.1056/NEJMoa1103151). The vaccine consisted of a soluble form of herpes simplex virus 2 (HSV-2) glycoprotein D (gD2) with adjuvant. The goal of the current study was to examine the composition of the humoral response to gD2 within a selected subset of vaccinated individuals. Serum samples from 30 vaccine recipients were selected based upon relative enzyme-linked immunosorbent assay (ELISA) titers against gD2; 10 samples had high titers, 10 had medium titers, and the remaining 10 had low ELISA titers. We employed a novel, biosensor-based monoclonal antibody (MAb)-blocking assay to determine whether gD2 vaccination elicited IgG responses against epitopes overlapping those of well-characterized MAbs. Importantly, IgGs from the majority of gD2-immunized subjects competed for gD binding with four antigenically distinct virus-neutralizing MAbs (MC2, MC5, MC23, and DL11). Screening of patient IgGs against overlapping peptides spanning the gD2 ectodomain revealed that about half of the samples contained antibodies against linear epitopes within the N and C termini of gD2. We found that the virus-neutralizing abilities of the 10 most potent samples correlated with overall gD-binding activity and to an even greater extent with the combined content of IgGs against the epitopes of MAbs MC2, MC5, MC23, and DL11. This suggests that optimal virus-neutralizing activity is achieved by strong and balanced responses to the four major discontinuous neutralizing epitopes of gD2. IMPORTANCE Several herpes simplex virus 2 (HSV-2) subunit vaccine studies have been conducted in human subjects using a recombinant form of HSV-2 glycoprotein D (gD2). Although several distinct, well-characterized virus-neutralizing epitopes on gD2 are targeted by murine monoclonal antibodies, it is not known whether the same epitopes are targeted by the humoral response to gD2 in humans. We have developed a novel, biosensor-based competition assay to directly address this important question. Using this approach, we identified epitopes that elicit strong humoral responses in humans, as well as other epitopes that elicit much weaker responses. These data provide new insight into the human response to known neutralizing gD2 epitopes and reveal characteristics of this response that may guide future vaccine development.